In vivo N2 Laser Effect on Lymphocyte Transformation Capacity and Phagocytosis Activity in Mice - Mahdi, Rasool A.; Hajim, Khalil I.; Hamodi, Salem R. (Iraqi Journal of Laser, 2006)
The objective of this in vivo study is to investigate the effects of 337.1 nm pulsed N2 laser on cellular immune response represented by lymphocyte transformation capacity and phagocytosis activity in laboratory animals. The samples include 60 adult male BALB/c mice, were divided into control group and experimental groups. The experimental groups were divided into two main groups according to the time period after N2 laser irradiation. Each group was divided into 9 subgroups which exposed to N2 laser radiation at different values of pulse repetition rates and exposure times. The results of immunological tests demonstrated that the exposure to 180 J/cm2 of N2 laser radiation induce adverse effect to cellular immune response. The results of lymphocyte transformation assay showed that the capacity of lymphocyte to be transformed as response to mitogen PHA decreased only in subgroups that treated with 180 J/cm2. While in the other subgroups the percent of transformed lymphocyte cells was unaffected. The findings of phagocytosis assay showed that the activity of phagocytic cells increased only in subgroups that treated with 80 J/cm2, and decreased in subgroups that treated with 120 and 180 J/cm2.